Sistem Informasi Akuntansi Pembiayaan Konsumtiv Pada PT. Bank BNI Syariah KC Jambi - Heriyani; Satria Bahar Hidayat (Journal of Applied Accounting And Business, 2020)
PT Bank BNI Syariah disbursed financing with various existing products, for the welfare of the people. PT. bank BNI Syariah promised that the funds collected by the people and would be utilized for the sake of the three other member of the community. PT Bank BNI Syariah at the time of distribution of financing. PT Bank BNI Syariah still uses the old method so it is less efficient becouse it only has to do simulations at the office. With this web-based application PT Bank BNI Syariah anywhere and anytime without having to print installment tables. The results achieved in the research of PT Bank BNI Syariah is a website based information system using Xampp, PHP and MySQl with this system is expected to be able to overcome existing problems and improve the quality of service to customers of PT Bank BNI Syariah. For PT BNI Syariah itself makes it easier for marketers to covecy financing simulations.